2007
DOI: 10.1109/tasc.2007.898889
|View full text |Cite
|
Sign up to set email alerts
|

Improvements of Current Decay Behavior of HTS Coils in Persistent Current Operations

Abstract: In order to improve the current decay behavior of high-temperature superconducting (HTS) coils using silversheathed Bi-2223 tapes in persistent current operations, the effect of the shielding current on the current decay behavior has been studied for magnetically levitated superconducting coils in internal ring devices. Generally, the current decay behavior of HTS coils is evaluated by the inductance of the HTS coils, the joint resistance and electric field versus current density relationship of the HTS tapes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…A remanent field was also reported by Gu et al [9], which was explained by a "finite thickness rectangular bar model" of the flux penetration. [10] Hemmi et al [11,12] reported a drift with time of the screening current-induced magnetic field. Recently, Amemiya and Akachi [13] conducted a general kind of numerical simulation on the steady state screening current-induced magnetic field for a 1.3 GHz NMR design.…”
Section: Introductionmentioning
confidence: 99%
“…A remanent field was also reported by Gu et al [9], which was explained by a "finite thickness rectangular bar model" of the flux penetration. [10] Hemmi et al [11,12] reported a drift with time of the screening current-induced magnetic field. Recently, Amemiya and Akachi [13] conducted a general kind of numerical simulation on the steady state screening current-induced magnetic field for a 1.3 GHz NMR design.…”
Section: Introductionmentioning
confidence: 99%
“…It involves dividing the HTS into small unit cells to analyze the current density and the magnetic field distributions in detail. Over the last few decades, various FEM methods have been proposed to analyze HTS devices, including the H-formulation [10,32,33], the A-V formulation [34,35], and the T-A formulation [36][37][38][39][40]. However, due to their underlying physical principles, these FEM methods are normally limited to studying the behavior of HTS components under pre-determined current profiles.…”
Section: Introductionmentioning
confidence: 99%
“…Since a spacecraft cannot be equipped with refrigerants, mostly because of mass considerations, the ac loss could become a serious problem for the reliability of an HTS coil. Moreover, the induced I s could have large effects on the magnetic field distribution and the current transport characteristics of the HTS coil [12][13][14][15]. These effects must be estimated to design optimal HTS coil systems for space missions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, understanding I s is highly important for terrestrial applications, e.g. magnetic resonance imaging, nuclear magnetic resonance imaging and cyclotrons, which require stable magnetic fields [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%